Variation in maternal and anxiety-like behavior associated with discrete patterns of oxytocin and vasopressin 1a receptor density in the lateral septum - Curley, JP (2012)
The relationship between anxiety and maternal behavior has been explored across species using a variety of approaches, yet there is no clear consensus on the nature or direction of this relationship. In the current study, we have assessed stable individual differences in anxiety-like behavior in a large cohort (n=57) of female F2 hybrid mice. Using open-field behavior as a continuous and categorical (high vs. low) measure we examined the relationship between the anxiety-like behavior of virgin F2 females and the subsequent maternal behavior of these females. In addition, we quantified oxytocin (OTR) and vasopressin (V1a) receptor density within the lateral septum to determine the possible correlation with anxiety-like and maternal behavior. We find that, though activity levels within the open-field do predict latency to engage in pup retrieval, anxiety-like measures on this test are otherwise not associated with subsequent maternal behavior. OTR density in the dorsal lateral septum was found to be negatively correlated with activity levels in the open-field and positively correlated with frequency of nursing behavior. V1a receptor density was significantly correlated with postpartum licking/grooming of pups. Though we do not find support for the hypothesis that individual differences in trait anxiety predict variation in maternal behavior, we do find evidence for the role of OTR and V1a receptors in predicting maternal behavior in mice and suggest possible methodological issues (such as distinguishing between trait and state anxiety) that will be a critical consideration for subsequent studies of the anxiety-maternal behavior relationship.